Quand l’homme devient nourriture : Leimoné dévorée par un cheval - Delattre, Charles (Food & History, 2015)
Abstract From an anthropological and structuralist perspective, it is easy to detect a number of stories in ancient Greece where man, who eats by nature in a civilized way, exchanges his position with his prey and either becomes a wild predator, or is eaten. The study of the character of Leimone, a girl eaten by a horse, allows us to specify under what conditions this reversal happens. The examination of the vocabulary used by different sources shows that the body, and not food, is the focus of these sources: Leimone’s story deals more with dismemberment and dispersal than with digestion. The texts, belonging to very different periods, tend to be quite explicit about these parallels which poses the question of redundancy. Abstract Dans une perspective anthropologique structurale, on peut analyser des récits en Grèce ancienne où l’homme, mangeur civilisé par nature, change de position avec sa proie en devenant soit mangeur sauvage, soit mangé. L’étude du personnage de Leimoné, jeune fille dévorée par un cheval, permet de préciser comment se fait ce renversement. Le vocabulaire utilisé par les sources montre que c’est le corps, non la nourriture, qui est au centre du dispositif énonciatif : l’écartèlement et la dispersion importent plus que la digestion. Les textes, d’époques diverses, explicitent les parallèles établis par l’analyse anthropologique, ce qui pose la question de sa redondance.